2011
DOI: 10.1074/jbc.m111.256644
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Matrix Metalloproteinase 14 (MMP-14)-mediated Cancer Cell Migration

Abstract: Matrix metalloproteinases (MMPs) have been shown to be key players in both extracellular matrix remodeling and cell migration during cancer metastasis. MMP-14, a membraneanchored MMP, in particular, is closely associated with these processes. The hemopexin (PEX) domain of MMP-14 has been proposed as the modulating region involved in the molecular cross-talk that initiates cell migration through homodimerization of MMP-14 as well as heterodimerization with the cell surface adhesion molecule CD44. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
202
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(206 citation statements)
references
References 52 publications
3
202
1
Order By: Relevance
“…They are involved in the degradation of the extracellular matrix (ECM) and play a role in the invasion and metastasis of tumor cells (3,4). Previous studies (36)(37)(38) have suggested that disruption to the ECM during tumor progression is due to an imbalance in the MMP/TIMP ratio. Our study revealed that a significant upregulation of MMP-9 and TIMP-1 protein expression in JEG-3 cells was observed following treatment with TGF-β1 at concentrations of 100 and 200 µg/l.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in the degradation of the extracellular matrix (ECM) and play a role in the invasion and metastasis of tumor cells (3,4). Previous studies (36)(37)(38) have suggested that disruption to the ECM during tumor progression is due to an imbalance in the MMP/TIMP ratio. Our study revealed that a significant upregulation of MMP-9 and TIMP-1 protein expression in JEG-3 cells was observed following treatment with TGF-β1 at concentrations of 100 and 200 µg/l.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion through collagen networks and subsequent collagenolysis relies principally on MMP-14, not on secreted MMPs (32). It has now been shown, that MMP-14 interacts with CD44, a membrane-associated glycoprotein, which has also been shown to be a cancer stem cell marker in HNSCC (31,55,56). By this interaction a migratory front is created, which enables the cells to migrate through the tissue in the direction led by MMP-14 (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has now been shown, that MMP-14 interacts with CD44, a membrane-associated glycoprotein, which has also been shown to be a cancer stem cell marker in HNSCC (31,55,56). By this interaction a migratory front is created, which enables the cells to migrate through the tissue in the direction led by MMP-14 (31). To minimize the remodeling of extracellular matrix necessary for tissue invasion, MMP-14 is localized at the leading edge of the cell, the invadopodia (31,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations